2011
DOI: 10.1002/pd.2660
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of early, intermediate and late pre‐eclampsia from maternal factors, biophysical and biochemical markers at 11–13 weeks

Abstract: Objective To develop models for prediction of pre-eclampsia (PE) based on maternal factors and biophysical and biochemical markers at 11-13 weeks' gestation.Methods Screening study of singleton pregnancies at 11-13 weeks including 752 (2.2%) that subsequently developed PE and 32 850 that were unaffected by PE. Models were developed for the prediction of early PE, requiring delivery before 34 weeks, intermediate PE with delivery at 34-37 weeks and late PE delivering after 37 weeks. The data used for the models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
409
5
26

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(474 citation statements)
references
References 40 publications
34
409
5
26
Order By: Relevance
“…One article was omitted as two studies were based on the same population and presented similar data, [16,27] with the article reporting more complete information included. [16] Characteristics of the eight included studies are presented in Table 3.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
“…One article was omitted as two studies were based on the same population and presented similar data, [16,27] with the article reporting more complete information included. [16] Characteristics of the eight included studies are presented in Table 3.…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%
“…Consequently, the measured concentrations of PAPP-A and PlGF must be adjusted for these variables before comparing results with pathological pregnancies. The MoM values of PAPP-A and PlGF are significantly reduced at 11-13 weeks' gestation in women who subsequently develop PE [3,18].…”
mentioning
confidence: 95%
“…A large number of biochemical markers have been investigated for a prediction of PE. Several biochemical markers (PAPP-A, PlGF, PP13, Sendoglin, Inhibin-A, Activin-A, Pentraxin 3 and P-Selectin) as potential predictors describe the foetal and placental endocrine functions and the maternal endothelial dysfunction [18]. Some studies are concluding that the major phenotype of PE, hypertension and proteinuria, may be due to an excess of circulating anti-antigenic growth factors, most notably soluble fms-like tyrosine kinase 1 (SFLT1) and soluble endoglin (SENG), and reduced levels of placental growth factor (PlGF) [19].…”
mentioning
confidence: 99%
“…It has also been shown that the risk for numerous pregnancy complications can be assessed around 12+ weeks of gestation. Screening for pre-eclampsia is of particular importance, as its prevalence of between 1 and 2% justifies screening, and as the individual risk for pre-eclampsia can be reduced through the administration of aspirin to patients with an increased risk [2,17]. The screening study of Akolekar et al, the most comprehensive study to date, investigated around 33 000 normal pregnancies and 752 pregnancies with subsequent pre-eclampsia in 11+ to 13+ weeks of gestation [17,39].…”
Section: Studymentioning
confidence: 99%
“…Screening for pre-eclampsia is of particular importance, as its prevalence of between 1 and 2% justifies screening, and as the individual risk for pre-eclampsia can be reduced through the administration of aspirin to patients with an increased risk [2,17]. The screening study of Akolekar et al, the most comprehensive study to date, investigated around 33 000 normal pregnancies and 752 pregnancies with subsequent pre-eclampsia in 11+ to 13+ weeks of gestation [17,39]. They found that a screening policy that was based on the combination of previous maternal history, maternal blood pressure, resistance in the uterine arteries, and the serum markers PAPP-A and PlGF provided detection rates of more than 85% of those pregnancies that resulted in pre-eclampsia prior to 34 weeks of gestation, with a false positive rate of 10%.…”
Section: Studymentioning
confidence: 99%